2001
DOI: 10.1007/s002640100242
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, iodine and fungal contamination in Yulin District (People's Republic of China) endemic for Kashin-Beck disease

Abstract: We studied the status of selenium, iodine and fungal contamination in 353 school children (age 5-14 years) from four rural villages in the District of Yulin. In three villages Kashin-Beck disease (KBD) was endemic, whereas there were no cases of KBD in the fourth village. Clinical, biological and radiological examinations (right hand) were performed and KBD was established by X-ray diagnosis. The prevalence rate of KBD was 30.2%, 44.2% and 45.3% in the three endemic villages. Mean hair selenium and urine iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…Some others factors have to play a role. A previous study has showed the role of fungal contamination of the barley [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some others factors have to play a role. A previous study has showed the role of fungal contamination of the barley [22].…”
Section: Discussionmentioning
confidence: 99%
“…In größeren epidemiologischen Studien sind Selenbestimmungen in Zehennä-geln erfolgreich zur Unterscheidung des Selenstatus der untersuchten Kollektive verwendet worden [4, 42,43], und auch Haare scheinen sich für den Vergleich von Kollektiven zu eignen [30,32]. Auch wenn ein Zusammenhang zwischen der Selenaufnahme und den Gehalten in Haaren besteht, eignen sich Haaranalysen nicht zur individuellen Diagnostik des Selenstatus [44,45].…”
Section: Selenunclassified
“…In China, the relevant research studies have been carried out since the 1950s. These studies focused mainly on environmental etiology of KBD, with an emphasis on the relationship between KBD prevalence and selenium levels in eco-environments or human body (Li et al 1982(Li et al , 1992Deng et al 1999;Guo et al 1999;Xu et al 2000;Zhang et al 2001;Wang et al 2003;Fan 2005), organic matter concentration in drinking waters (Wu et al 1987;Peng and Xu 1988;Wang and Feng 1989;Zhang et al 1990; Wang et al 1991a, b) and severe contamination of grains by fungi-produced mycotoxin (Bi et al 2001).…”
Section: Introductionmentioning
confidence: 99%